2019
DOI: 10.1038/s41598-019-50807-8
|View full text |Cite
|
Sign up to set email alerts
|

Oral selective serotonin reuptake inhibitors activate vagus nerve dependent gut-brain signalling

Abstract: The vagus nerve can transmit signals to the brain resulting in a reduction in depressive behavior as evidenced by the long-term beneficial effects of electrical stimulation of the vagus in patients with intractable depression. The vagus is the major neural connection between gut and brain, and we have previously shown that ingestion of beneficial bacteria modulates behaviour and brain neurochemistry via this pathway. Given the high levels of serotonin in the gut, we considered if gut-brain signaling, and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 50 publications
0
64
0
Order By: Relevance
“…Moreover, as suggested by preclinical research, stimulation at the left ear exerts stronger effects on invigoration when food rewards are at stake. We conclude that taVNS may provide a promising brain stimulation technique to acutely improve motivational syndromes characterized by a lack of vigor to pursue rewards such as apathy 55,59 or anhedonia 60 as these symptoms might be partly caused by aberrant vagal signaling 61,62 . Notwithstanding, it is unknown to date whether acute improvements can predict sustained therapeutic effects of potential taVNS-based treatments, which remains as a vital question for the translation to clinical settings.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, as suggested by preclinical research, stimulation at the left ear exerts stronger effects on invigoration when food rewards are at stake. We conclude that taVNS may provide a promising brain stimulation technique to acutely improve motivational syndromes characterized by a lack of vigor to pursue rewards such as apathy 55,59 or anhedonia 60 as these symptoms might be partly caused by aberrant vagal signaling 61,62 . Notwithstanding, it is unknown to date whether acute improvements can predict sustained therapeutic effects of potential taVNS-based treatments, which remains as a vital question for the translation to clinical settings.…”
Section: Discussionmentioning
confidence: 98%
“…Beyond the heart, research should address the consequences of decreased vagal activity including the systematic investigation of different organs. Preliminary research in animals has shown, that subdiaphragmatic vagotomy abolishes the antidepressive effects of pharmacological treatment with selective serotonin reuptake inhibitors (Neufeld et al, 2019). It is research like this that questions our current understanding and conceptualization of psychiatric disorders.…”
Section: Some Conclusionmentioning
confidence: 99%
“…Some of these metabolites participate in the gutbrain axis activity with potential to modulate central physiological and pathologic processes. Mechanisms potentially include binding to host receptors in the brain, stimulation of vagus nerve in the gut, alteration of central neurotransmission, and modulation of neuroinflammation [8,9]. Microbiota-gut-brain axis signaling can occur via several pathways including the immune system, recruitment of host neurochemical signaling, direct enteric nervous system routes and the vagus nerve, and the production of bacterial metabolite such as short-chain fatty acids, branchedchain amino acids, and peptide glycans [10,11].…”
Section: The Role Of Gut Microbiotamentioning
confidence: 99%
“…This vagal activity appears to have protective properties on the intestinal barrier, inflammatory mechanisms, and the microbiome. This potentially useful pathway deserves to be explored therapeutically [8,13].…”
Section: The Role Of Gut Microbiotamentioning
confidence: 99%